1988
DOI: 10.1093/clinchem/34.8.1610
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid concentrations in serum and aqueous humor from subjects with extreme myopia or senile cataract.

Abstract: With an amino acid analyzer, we measured amino acids and related compounds in serum and aqueous humor from normal Chinese and some patients with extreme myopia or senile cataracts. Forty peaks were well resolved, and their areas were used to quantify each compound. In the myopic patients, glutamate, alpha-aminoadipate, and methionine concentrations in serum were 10-fold those in the normal subjects. Values for most of the other amino acids and related compounds were also higher in myopic patients' sera. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Additionally, some of the amino acids profiled (phenylalanine, leucine, isoleucine, valine, alanine and threonine) were previously reported as important markers of extreme myopia and senile cateract in AH, measured using an amino acid analyzer [17].…”
Section: Characterization Of the Profilementioning
confidence: 99%
“…Additionally, some of the amino acids profiled (phenylalanine, leucine, isoleucine, valine, alanine and threonine) were previously reported as important markers of extreme myopia and senile cateract in AH, measured using an amino acid analyzer [17].…”
Section: Characterization Of the Profilementioning
confidence: 99%
“…Because blood aspartate levels (0-15 uM) 16,17 do not allow adequate aspartate import in most cell types, aspartate availability and aspartate-derived nucleotide synthesis depend on mitochondrial respiration and TCA cycle flux. We and others 1,[18][19][20] have shown that ETC impairment leads to inhibition of mTORC1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Aspartate is required for both purine and pyrimidine de novo synthesis. As Blood aspartate level in human is very low [48] and uptake of aspartate may be not sufficient for cell proliferation, a primary function of respiration in proliferating cell was found to support aspartate biosynthesis, ensuring cancer cell survival and proliferation [49, 50].…”
Section: Metabolic Co-dependency Shaped By Environmentmentioning
confidence: 99%